2005
DOI: 10.1088/0029-5515/45/8/010
|View full text |Cite
|
Sign up to set email alerts
|

Ion kinetic effect on bifurcated relaxation to a field-reversed configuration in TS-4 CT experiment

Abstract: Ion kinetic effect on the bifurcated relaxation of merging spheromaks to a field-reversed configuration (FRC) was studied experimentally using varied € S * which is the ratio of the minor radius to the ion skin depth from 1 to 7. The two merging spheromaks were observed to relax to an FRC or a new spheromak depending on whether the initial poloidal eigen value was smaller or larger than a threshold value. The threshold initial poloidal eigen value for the relaxation to an FRC increased with decreasing € S * va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…FRC have been formed by counter.helicity merging of two spheromaks (the helicity concept is introduced in the next section). TS-3 has been recently upgradede in the TS-4 facility (Kawamori (2004)) .…”
Section: Open Issues In Frc Researchmentioning
confidence: 99%
“…FRC have been formed by counter.helicity merging of two spheromaks (the helicity concept is introduced in the next section). TS-3 has been recently upgradede in the TS-4 facility (Kawamori (2004)) .…”
Section: Open Issues In Frc Researchmentioning
confidence: 99%
“…Spheromak merging was first studied on the TS-3 device at the University of Tokyo in the late 1980's and then further developed on the MRX device in 1990's [15][16][17][18][19][20][21][22]. These TS-3 and MRX experiments demonstrated that the plasma merging formation scheme could successfully produce both spheromaks and FRCs.…”
Section: Formation Of Frc By Spheromak Mergingmentioning
confidence: 99%
“…This configuration utilizes a stabilizing shell and neutral beam injection with a practically broad velocity distribution [10]. Slow formation of an FRC plasma by the merging of spheromak plasmas has been successfully demonstrated in a number of experiments as described above [15][16][17][18][19][20][21]. The experimental observation of the co-interchange instability in MRX [24] yields further motivation for the NBI system included in the SPIRIT concept.…”
Section: Spirit Conceptmentioning
confidence: 99%
“…Field reversals up to 200 G have been obtained by applying an RMF to pre-ionized plasma in a uniform axial field of 150 G. Although the temperature was relatively low (40 eV), the slow formation of FRC plasmas was clearly demonstrated. An alternative method is based on the merging of counter-helicity spheromaks, a method developed at TS-3/4 [14][15][16][17][18][19][20], as shown in Fig. 4.…”
Section: Recent Advances In Frc Experimentsmentioning
confidence: 99%